Experts within Democracy: The Turner Version. (June 2015) - Agassi, Joseph
Stephen Turner defends the sociopolitical role that experts—mainly but not only of the scientific kind—play in modern democratic society and explores means for increasing the rationality of their employment. Laudable though this is, at times Turner goes into more detail than democratic principles require; in his enthusiasm for rationality, he aims at levels of adequacy that are not always within the grasp of democracy.